EFFECT OF ORGANIC MANURES ON MULBERRY LEAF FIELD AND COCOON CHARACTERS OFSILKWORM, BOMBYX MORI L. (International Journal of Food and Nutritional Sciences, 2022)
The study was conducted in the zoology department of Muslim Arts College,Thiruvithancode, Kanyakumari District, Tamil Nadu, to ascertain the impact of applyingvarious organic manures (farmyard manure and vermicompost, both separately and incombination) to the soil in mulberry trees, as well as the effects on the characteristics ofsilkworm larvae and cocoons